THE OXCART MEN IN THE NORTH-WEST CENTRAL REGION OF THE CENTRAL VALLEY OF COSTA RICA AMONG THE CENTURIES XIX AND XX - Rodríguez Sancho, Javier (2014)
This article analyzes a piece of national history related to Costa Rican rural means of transportation in the XIX and XX centuries. Particulary, the study focuses on the North-West Central Region of this country that groups the cantons of San Ramón, Palmares, Naranjo, Grecia, Valverde Vega, Poás, Atenas y Zarcero, where the “boyero” helped develop the rural economy by offering their transport services from town to town.